2009
DOI: 10.1007/s00265-009-0871-x
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphology, swimming velocity, and longevity in the house sparrow Passer domesticus

Abstract: Sperm competition exerts strong selection on males to produce spermatozoa with an optimal morphology that maximizes their fertilization success. Long sperm were first suggested to be favored because they should swim faster. However, studies that investigated the relationship between sperm length and sperm competitive ability or sperm swimming velocity yielded contradictory results. More recently, ratios of the different sections of a spermatozoon (the head, midpiece, and flagellum) were suggested to be more cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 51 publications
7
77
0
1
Order By: Relevance
“…Yet even this trait appears to be inconsistently associated with sperm velocity, even within a single species (e.g. Helfenstein et al 2010;Cramer et al 2015). Similarly, in the current study we found the ratio of flagellum to head length was positively correlated with sperm velocity in P. a. hecki, but not P. a. acuticauda.…”
Section: Sperm Traitsupporting
confidence: 58%
“…Yet even this trait appears to be inconsistently associated with sperm velocity, even within a single species (e.g. Helfenstein et al 2010;Cramer et al 2015). Similarly, in the current study we found the ratio of flagellum to head length was positively correlated with sperm velocity in P. a. hecki, but not P. a. acuticauda.…”
Section: Sperm Traitsupporting
confidence: 58%
“…Previous studies have examined correlations between sperm design and sperm function [7,38,39] and their role as determinants of fertilization success [3,4,12]. However, although some studies showed significant correlations between these traits, others found no evidence for these associations [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in birds and mammals have reported relationships between sperm length and velocity ( 798 J. L. Fitzpatrick et al Sperm length influences sperm velocity et al 2009;Helfenstein et al 2010). However, most studies have failed to reveal such patterns (Humphries et al 2008), possibly because the traditional approach of analysing sperm length and velocity using different samples of sperm underestimates the covariance between sperm length and velocity at the within-and among-male levels.…”
Section: Discussionmentioning
confidence: 99%